Estradiol rapidly increases GluA2‐mushroom spines and decreases GluA2‐filopodia spines in hippocampus CA1. Issue 12 (28th August 2017) - Avila, Jorge A.; Alliger, Amber A.; Carvajal, Brigett; Zanca, Roseanna M.; Serrano, Peter A.; Luine, Victoria N.
Abstract: Hippocampal dendritic spine density rapidly increases following estradiol (E2 ) treatment, but the types of spines and trafficking of synaptic markers have received little investigation. We assessed rapid effects of E2 over time on the density of four spine types (stubby, filopodial, long thin, and mushroom) and trafficking of AMPA receptor subunit GluA2 and PSD95 on tertiary, apical dendrites in CA1. Castrated male rats received 20 μg kg −1 of E2 or vehicle and were sacrificed 30 or 120 min later. Images of Golgi‐Cox impregnated and PSD95/GluA2 stained dendrites were captured under the confocal microscope and quantified with IMARIS‐XT. Stubby and filopodial spine densities did not change following treatment. Long‐thin spines significantly decreased at 30 min while mushroom spines significantly increased at 120 min. GluA2, PSD95, and GluA2/PSD95 colocalization levels in stubby or long thin spines did not change, but filopodial spines had significantly reduced GluA2 levels at 30 min. Mushroom spines showed significantly increased levels for GluA2, PSD95 and GluA2/PSD95 colocalization at 120 min. Because GluA2 is important for memory consolidation, current results present novel data suggesting that trafficking of GluA2 to mushroom spines provides one mechanism contributing to estradiol's ability to enhance learning and memory by the PI3 signaling pathway.